Krasūang Rǣngngān kap kānkǣkhai panhā kānkhā manut nai Prathēt Thai (Samnakngān Palat Krasūang Rǣngngān, 2008)
On measures taken by the Ministry of Labour of Thailand in solving and preventing human trafficking.